2012
DOI: 10.1111/cmi.12058
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortusinduces intracellular retention of MHC-I molecules in human macrophages down-modulating cytotoxic CD8+T cell responses

Abstract: SummaryBrucella abortus elicits a vigorous Th1 immune response which activates cytotoxic T lymphocytes. However, B. abortus persists in its hosts in the presence of CD8 + T cells, establishing a chronic infection. Here, we report that B. abortus infection of human monocytes/macrophages inhibited the IFN-g-induced MHC-I cell surface expression. This phenomenon was dependent on metabolically active viable bacteria. MHC-I down-modulation correlated with the development of diminished CD8 + cytotoxic T cell respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 59 publications
3
59
0
Order By: Relevance
“…In our laboratory, we demonstrated that B. abortus infection inhibits MHC-I and MHC-II expression induced by IFN-␥, contributing in this way to the chronicity of Brucella infection (43,44). Our results indicated that DHEA immune intervention could positively affect monocyte function, resulting in a significant recovery of the inhibited IFN-␥-induced MHC-I and -II expression mediated by B. abortus infection.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our laboratory, we demonstrated that B. abortus infection inhibits MHC-I and MHC-II expression induced by IFN-␥, contributing in this way to the chronicity of Brucella infection (43,44). Our results indicated that DHEA immune intervention could positively affect monocyte function, resulting in a significant recovery of the inhibited IFN-␥-induced MHC-I and -II expression mediated by B. abortus infection.…”
Section: Discussionmentioning
confidence: 59%
“…IFN-␥ has a critical role in protective immunity against Brucella (6, 7). The strategies that allow B. abortus to survive for prolonged periods inside macrophages could be explained at least in part by the inhibition of the IFN-␥-induced expression of MHC-I and MHC-II molecules (43,44). We hypothesized that this phenomenon could be modulated by cortisol and DHEA.…”
Section: Dhea and Cortisol In Brucellosis Patientsmentioning
confidence: 99%
“…Both cell-intrinsic (stunted IFN-␥ production and delayed increase in the number of IFN-␥-producing cells) and cell-extrinsic factors due to an environment of chronic infection were found to affect the ability of CD8 ϩ T cells to control chronic brucellosis. Current vaccine constructs do not generate a viable CD8 ϩ T cell immune response and moreover ignore CD8 ϩ T cell-mediated immunological memory because these cells have been considered unimportant in the control of human infection (34). An understanding of how to rescue exhausted CD8 ϩ T cells may be critical to decreasing the incidence of reactivation and reinfection, even after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, while CD8 T cells can be cytotoxic (in addition to producing IFN-γ) and such cytotoxic cells have been demonstrated to be generated in vivo following infection, a clear role for cytotoxic cells is not evident (29). Finally, infection of human macrophages resulted in decreased major histocompatibility complex (MHC) class I molecules on the surface, and thus decreased Brucella antigen presentation to CD8 T cells and decreased killing (32).…”
Section: Insights Into Anti-brucella Immune Responsesmentioning
confidence: 99%